Pengaruh Pupuk Organik Cair (POC) dari Sampah Rumah Tangga terhadap Pertumbuhan Tanaman Anggrek (Dendrobium sp.) Secara In Vitro - Ali Imran; Ida Royani; Iwan Doddy Dharmawibawa (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2022)
This study aims to obtain the right formula for using Liquid Organic Fertilizer (LOF) from household waste for the growth of Dendrobium sp. The method used was an experiment with a Completely Randomized Design (CRD), with three replications. The medium used is MS media by adding liquid organic fertilizer from household waste with a concentration of (0-3) mg/L. Parameters in this study were the fastest day of emergence of shoots, number of shoots, and roots. The data obtained was analyzed using the Kruskal-Wallis test, because the data obtained was not normal and not homogeneous, a descriptive analysis was used. The results showed that the highest number of shoots was obtained at a concentration of 3 mg/L of organic waste growth regulator with a total of 4.3 shoots and 15.7 roots at a concentration of 2 mg/L the fastest day for shoots to appear after planting was 12 days on plant media and roots appeared on 8th day after planting on Dendrobium sp.